2011
DOI: 10.1007/s00284-011-9880-x
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Enterococci in Animal Meat and Faeces and Co-Transfer of Resistance from an Enterococcus durans to a Human Enterococcus faecium

Abstract: Forty-eight isolates resistant to at least two antibiotics were selected from 53 antibiotic-resistant enterococci from chicken and pig meat and faeces and analysed for specific resistance determinants. Of the 48 multidrug-resistant (MDR) strains, 31 were resistant to two antibiotics (29 to erythromycin and tetracycline, 1 to erythromycin and vancomycin, 1 to vancomycin and tetracycline), 14 to three (erythromycin, tetracycline and vancomycin or ampicillin) and 3 to four (erythromycin, vancomycin, ampicillin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 32 publications
3
56
0
2
Order By: Relevance
“…Vignaroli et al [48] investigated isolates of enterococci co-resistant to tetracycline and erythromycin originating from meat and faeces of chickens and pigs. They found that under in vitro conditions the isolates from faeces more readily transferred the resistance to enterococci of human origin.…”
Section: Transmission Of Tetracycline and Mls Resistancementioning
confidence: 99%
“…Vignaroli et al [48] investigated isolates of enterococci co-resistant to tetracycline and erythromycin originating from meat and faeces of chickens and pigs. They found that under in vitro conditions the isolates from faeces more readily transferred the resistance to enterococci of human origin.…”
Section: Transmission Of Tetracycline and Mls Resistancementioning
confidence: 99%
“…Enterococcal infections, particularly nosocomial infections, may be life threatening in humans, as antibiotic treatment of these infections is difficult (6). In the veterinary medicine field, antibiotics are commonly used for the control and treatment of diseases, and antibiotic usage results in a selection of resistant enterococci in the intestinal flora of animals.…”
Section: Introductionmentioning
confidence: 99%
“…In the veterinary medicine field, antibiotics are commonly used for the control and treatment of diseases, and antibiotic usage results in a selection of resistant enterococci in the intestinal flora of animals. Antibiotic resistant isolates can pass to humans either by food products or direct contact, and antibiotic resistance genes on mobile genetic elements may be transferred to human bacteria (6).…”
Section: Introductionmentioning
confidence: 99%
“…são propensos a sofrer seleção a cada administração de antimicrobiano, levando à formação de um reservatório animal de Enterococcus spp. resistentes, que podem infectar os seres humanos tanto por contato direto com animais como através da ingestão de alimentos de origem animal (Kaszanyitzky et al 2007, Oliveira et al 2010, Vignaroli et al 2011. No trato gastrintestinal, os genes de resistência adquiridos podem ser transferidos por elementos móveis de DNA, tanto para outros da espécie como outros agentes zoonóticos, mesmo que em testes de antibiograma os Enterococcus não apresentem resistência (Bogaard et al 2002, Cauwerts et al 2007.…”
Section: Introductionunclassified